Predicting recovery from acute severe asthma. Issue 11 (November 1981) - Jenkins, P F; Benfield, G F; Smith, A P
Abstract : Fifty-two patients admitted to hospital with acute severe asthma took part in a prospective study investigating the rate and pattern of their subsequent recovery. Clinical assessment of the severity of the acute attack on admission (according to pulse rate, degree of pulsus paradoxus, and peak expiratory flow rate) did not reliably predict the results of arterial blood gas analysis. Subjects were divided into three groups according to the speed of recovery of peak expiratory flow rate. Historical features associated with slow recovery were: age over 40 years, non-atopic asthma, a longer duration of the acute attack before hospital admission, poor long-term control of asthma, and the use of maintenance oral corticosteroids. The degree of pulsus paradoxus on admission and the improvement in PEFR at six hours and arterial oxygen tension (PaO2) at 48 hours were also useful in predicting speed of recovery. The severity of the attack, assessed on admission by arterial blood gas analysis and PEFR, did not differ between the three groups of recovering patients. Hyperinflation was still present in 15 out of 44 patients investigated five days after admission even though PEFR had returned to mre than 80% of predicted normal in seven of these 15 subjects. The recovery of hypoxia was also commonly delayed with 12 out of 52 patients having PaO2 values of less than 80 mmHg at five days. Persistent hypoxia was more common in those with delayed delayed recovery PEFR.